Involvement of the endocannabinoid system in attentional modulation of nociceptive behaviour in rats. (15th December 2014) - Ford, G.K.; Moriarty, O.; Okine, B.N.; Tully, E.; Mulcahy, A.; Harhen, B.; Finn, D.P.
Abstract Background Distraction is used clinically to relieve and manage pain. It is hypothesized that pain demands attention and that exposure to another attention‐demanding stimulus causes withdrawal of attention away from painful stimuli, thereby reducing perceived pain. We have recently developed a rat model that provides an opportunity to investigate the neurobiological mechanisms mediating distraction‐induced analgesia, as these mechanisms are, at present, poorly understood. Given the well‐described role of the endogenous cannabinoid (endocannabinoid; EC) system in the modulation of pain and attentional processing, the present study investigated its role in distraction‐induced antinociception in rats. Methods Animals received the CB1 receptor antagonist/inverse agonist, rimonabant or vehicle intraperitoneally, 30 min prior to behavioural evaluation. Formalin‐evoked nociceptive behaviour was measured in the presence or absence of a novel‐object distractor. Liquid chromatography‐tandem mass spectrometry was used to determine the levels of the endogenous cannabinoids anandamide and 2‐arachidonoylglycerol (2‐AG) in the ventral hippocampus (vHip). Results Exposure to a novel object distractor significantly reduced formalin‐evoked nociceptive behaviour. The novel object‐induced reduction in nociceptive behaviour was attenuated by rimonabant. Novel object exposure was also associated with increased tissue levels of anandamide and 2‐AG in the vHip. Conclusions These data suggest that the reduction in formalin‐evoked nociceptive behaviour that occurs as a result of exposure to a novel object may be mediated by engagement of the EC system, in particular in the vHip. The results provide evidence that the EC system may be an important neural substrate subserving attentional modulation of pain.